Предмет: Алгебра,
автор: dkjfg
по алгебре. срочно нужно решение. даю 15 балов!
Приложения:
Ответы
Автор ответа:
0
верх сворачивается в формулу
(√z-2)² = (√z-2) (√z-2) вторая степень обозначает две такие скобки
А снизу 4-Z= -(Z-4) = -(√Z-2)(√Z+2)
(( √Z-2) (√Z-2) ) / - (√Z-2) (√Z+2) =
=
(√z-2)² = (√z-2) (√z-2) вторая степень обозначает две такие скобки
А снизу 4-Z= -(Z-4) = -(√Z-2)(√Z+2)
(( √Z-2) (√Z-2) ) / - (√Z-2) (√Z+2) =
=
Похожие вопросы
Предмет: Химия,
автор: Аноним
Предмет: Литература,
автор: ruslanediev25
Предмет: Химия,
автор: KosmoMix
Предмет: Биология,
автор: Mlukashova
Предмет: Литература,
автор: Виасава